A Weyward Witches’ Flight: The Digital Dérive as Place-Making Practice - Molloy Murphy, Angela; Pascoe, Joanna; Sturm, Sean (Brill, 2026)
At the intersection of visual, walking and dialogic pedagogies, this essay melds images, poems, conversations, stories and theories, wandering and wondering in public places like campuses and parks as the promptings of a desire for new becomings through autopoietic, technic and Gaian interconnections. It embodies the possibilities of the dérive, mediated through the digital (WhatsApp, Google Docs, Zoom and the Verbasiser) and our digits (texting, typing and mapping), as a method of place-making critical-creative practice open to transcultural and transpecific alliances that presage new ways of being-with places and peoples.
Keywords: 3901 Curriculum and pedagogy; visual essay; dérive; walking methodology; place-making; response-ability